Pregnancy in bicornuate uterus - Borgohain, D.; Srivastava, Shubhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
The incidence of the uterine malformations is estimated to be 3% to 5% in the general population. Abnormal fusion of the mesonephric duct (Mullerian duct) during embryonic life results in a variety of congenital uterine malformations like septate uterus, unicornuate uterus, and bicornuate uterus. Fertility and evolution of pregnancy depends on the type of uterine anomaly. Many of them are asymptomatic but it is important to consider this diagnosis in recurrent miscarriages, preterm labours, malpresentations, and intrauterine growth restrictions. We are presenting a 22-years-old pregnant woman with a history of abortion. The patient was not diagnosed with a bicornuate uterus in her first pregnancy. However, she was diagnosed with a bicornuate uterus based on the findings of ultrasound in the present pregnancy. A successful caesarean section was performed on the subject in the 39th week of gestation. According to the results, successful outcome could be achieved in patients with bicornuate uterus.